Positive trends in Southern Hemisphere carbonyl sulfide. Issue 21 (6th November 2015) - Kremser, Stefanie; Jones, Nicholas B.; Palm, Mathias; Lejeune, Bernard; Wang, Yuting; Smale, Dan; Deutscher, Nicholas M.
Abstract: Transport of carbonyl sulfide (OCS) from the troposphere to the stratosphere contributes sulfur to the stratospheric aerosol layer, which reflects incoming short‐wave solar radiation, cooling the climate system. Previous analyses of OCS observations have shown no significant trend, suggesting that OCS is unlikely to be a major contributor to the reported increases in stratospheric aerosol loading and indicating a balanced OCS budget. Here we present analyses of ground‐based Fourier transform spectrometer measurements of OCS at three Southern Hemisphere sites spanning 34.45°S to 77.80°S. At all three sites statistically significant positive trends are seen from 2001 to 2014 with an observed overall trend in total column OCS at Wollongong of 0.73 ± 0.03%/yr, at Lauder of 0.43 ± 0.02%/yr, and at Arrival Heights of 0.45 ± 0.05%/yr. These observed trends in OCS imply that the OCS budget is not balanced and could contribute to constraints on current estimates of sources and sinks. Key Points: First observed positive trend in OCS in the Southern Hemisphere Observed trends indicate imbalanced OCS budget Temporal structure of trend is similar across middle‐ and high‐latitude sites